2012
DOI: 10.6061/clinics/2012(11)09
|View full text |Cite
|
Sign up to set email alerts
|

Increased IgE serum levels are unrelated to allergic and parasitic diseases in patients with juvenile systemic lupus erythematosus

Abstract: OBJECTIVE:The aim of this study was to assess the IgE serum levels in juvenile systemic lupus erythematosus patients and to evaluate possible associations with clinical and laboratory features, disease activity and tissue damage.METHODS:The IgE serum concentrations in 69 consecutive juvenile systemic lupus erythematosus patients were determined by nephelometry. IgG, IgM and IgA concentrations were measured by immunoturbidimetry. All patients were negative for intestinal parasites. Statistical analysis methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…The total serum IgE levels did not statistically differ with respect to the SLEDAI-2K score (at the baseline, r = 0.16, p = 0.147; at the 18th month, r = 0.21, p = 0.057; at the end of follow-up, r = -0.03, p = 0.81, respectively; Fig 2). Our research was in accordance with recent studies, which suggested that increased serum IgE levels were unrelated to allergic diseases and disease activity in patients with JSLE or adult SLE [34][35][36]. However, the diagnosis of atopy in our study was based on patients' specific-IgE or SPT, which is evidently different from the total IgE.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The total serum IgE levels did not statistically differ with respect to the SLEDAI-2K score (at the baseline, r = 0.16, p = 0.147; at the 18th month, r = 0.21, p = 0.057; at the end of follow-up, r = -0.03, p = 0.81, respectively; Fig 2). Our research was in accordance with recent studies, which suggested that increased serum IgE levels were unrelated to allergic diseases and disease activity in patients with JSLE or adult SLE [34][35][36]. However, the diagnosis of atopy in our study was based on patients' specific-IgE or SPT, which is evidently different from the total IgE.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, JSLE patients with atopy at the disease onset had markedly higher total serum IgE and no evident difference in total serum IgE was observed at the end of follow-up. Elevated total serum IgE levels have been described in patients with SLE that are driven by the aberrant production of interferon and self-damaging autoantibodies [35]. Thus, we analyzed the correlations between total serum IgE and SLE-DAI-2K at the baseline, 18th month, and end of the follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the clinicallaboratory database and biorepository was established it has collaborated on 44 presented abstracts, two dissertations, three theses, eight published articles and five ongoing research projects. 3,4,[8][9][10][11][12][13][14][15] What are the most valuable/highest priority cases in your biobank?…”
Section: Example Output Statisticsmentioning
confidence: 99%
“…In addition, researchers have used clinical-laboratory information and human biological samples collected by this facility, resulting in a series of works. 3,4,[8][9][10][11][12][13][14][15] Therefore, as a pioneer initiative, this clinical-laboratory database and biorepository will supply researchers with important information and an apparatus that can illuminate the causative factors of autoimmune diseases and primary immunodeficiencies. …”
Section: Introductionmentioning
confidence: 99%